Refleksi Pelaksanaan Program Transformasi Digital di Masa Pandemi - Andhika Giri (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: This paper contains a reflection on the implementation of community service carried out by team during the pandemic era (2019 - 2022). Methodology/approach: Work program designed related to the use of information technology. Meanwhile, the contextual issues provided are community economics, education, archive management, and social media and websites optimalization Results/findings: Some challenges are faced during the implementation such as the limited ability to operate technology, limited internet connections, and the need for supporting devices. However, in general, the public understands the importance of innovation using technology as an effort to improve the effectiveness and efficiency of business processes. Conclusion: Even though it takes a long time in order to transform the manual method to technology-based. It takes active participation from the community to learn and consistence. In addition, assistance is also needed so the sustainability of digital transformation will continues as expected.